Educational paradigms in islamic medical history: A review - Mohammad R Asad; Mohammed Almansour; Syed Y Kazmi; Raed E Alzahrani; Mohammad M Ahmed; Mohammed Nazeer (Wolters Kluwer Medknow Publications, 2024)
The rise of Islam in Arabia witnessed a scientific pursuit from 8th CE to 14th CE in its vast dominion. Medicine was one among many disciplines that was reshaped during the golden ages of Islamic world. Physicians and scholars from diverse faiths and background flocked in learning centers of Baghdad, Cordoba, and other cities. A multicultural environment of medical research was evolved with fundings from state. From medical teaching and clinical training to the licensing of physicians, many of the modern attributes of medical education were pioneered in Islamic world. The scholarly transfusion from European territories of Islamic world to the Western world in medieval era laid the foundation of modern medical education.